Literature Review: Cause Factor Analysis and an Effort to prevent Medication Administration Error (MAE) at Hospital - Brigitta, Innes Rizma; Dhamanti, Inge (Unnes Journal of Public Health, 2020)
The high number of medical errors, especially in medication administration errors (MAE) in the last few decades that have occurred in hospitals in developed and developing countries makes patient safety an important issue. This requires the hospital to take steps that prioritize patient safety by focusing on preventive measures, so as to reduce the risk of an MAE. The writing of this article of literature review aims to explain the determinants of MAE in hospitals and their prevention efforts through preventive measures, so that patient safety standards in hospitals (zero defects) can be achieved. The design of the article search in this literature study was carried out through Google scholar, JAKI, and PSNet with the keywords of patient safety incident, medication administration error, contributing factor of MAEs, and determinant factor of MAEs. Based on 13 articles that have been obtained in accordance with the criteria, there are 38 determinant factors in MAE which are grouped into three categories, namely ineffective communication factors, work environment factors, and human factors. Various preventive efforts that can be done to prevent MAEs include: implementing crew resource management, clarifying the chain of command, using the communication form of SBAR, designing an ergonomic workplace, implementing Patient Advocacy Reporting System (PARS), providing training and education for health workers, and setting work schedules that do not exceed workload. Implementation of effective MAE preventive measures can reduce the number of MAEs in the hospital directly.